Synthesis and physical properties of a ball-like three-dimensional π-conjugated molecule - Kayahara, Eiichi; Iwamoto, Takahiro; Takaya, Hikaru; Suzuki, Toshiyasu; Fujitsuka, Mamoru; Majima, Tetsuro; Yasuda, Nobuhiro; Matsuyama, Naoto; Seki, Shu; Yamago, Shigeru (Nature communications, 2013)
Curved π-conjugated molecules with closed and three-dimensional (3D) structures, such as fullerenes and carbon nanotubes, have been the subject of intensive research due to their potential applications in molecular electronics. However, basic molecular skeletons of 3D molecules are limited because of the lack of a rational and selective synthetic method by organic synthesis. Here we report the synthesis of a 3D π-conjugated molecule based on the platinum-mediated assembly of four molecules of a stannylated trisubstituted benzene derivative forming a hexanuclear platinum complex with an octahedral shape, from which reductive elimination of platinum gave the target molecule. As many supramolecular transition metal–ligand complexes with 3D cages and polyhedral structures have been synthesized by self-assembly of ligands and metals, the current assembly/reductive elimination strategy could provide a variety of new 3D π-conjugated molecules with different structures and topologies, which are challenging to obtain using conventional synthetic methods. Curved π-conjugated compounds, such as the fullerenes, have a variety of practical uses in addition to being structurally striking. Here, the authors demonstrate metal-mediated assembly and subsequent reductive elimination as an elegant synthetic route to a fully conjugated ball-like molecule.